Differential Equations and Linear Algebra (4th Edition)

Published by Pearson
ISBN 10: 0-32196-467-5
ISBN 13: 978-0-32196-467-0

Chapter 1 - First-Order Differential Equations - 1.1 Differential Equations Everywhere - Problems: 5


The answer requires a proof as shown below.

Work Step by Step

Lets determine the right hand side of the equation first (RHS). $y^{'}$ = 1/t $y^{''}$ = -1/$t^{2}$ $y^{'''}$ = 2/$t^{3}$ = RHS Now lets determine the left hand side of the equation (LHS). 2$(y^{'})^{3}$ = 2($(1/t)^{3}$ = 2/$t^{3}$ = LHS As LHS = RHS, the equation is satisfied.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.